Scaffolded Antigens in Yeast Cell Particle Vaccines Provide Protection against Systemic Polyoma Virus Infection - Donald J. Tipper; Eva Szomolanyi-Tsuda (Journal of Immunology Research)
Background. U65, a self-aggregating peptide scaffold, traps fused protein antigens in yeast cells. Conversion to Yeast Cell Particle (YCP) vaccines by partial removal of surface mannoproteins exposes β-glucan, mediating efficient uptake by antigen-presenting cells (APCs). YCP vaccines are inexpensive, capable of rapid large-scale production and have potential for both parenteral and oral use. Results. YCP processing by alkaline hydrolysis exposes up to 20% of the glucan but converts scaffolded antigen and internal yeast proteins into a common aggregate, preventing selective yeast protein removal. For U65-green fluorescent protein (GFP) or U65-Apolipoprotein A1 (ApoA1) subcutaneous vaccines, maximal IgG responses in mice required 10% glucan exposure. IgG responses to yeast proteins were 5-fold lower. Proteolytic mannoprotein removal produced YCPs with only 6% glucan exposure, insufficiently porous for selective removal of even native yeast proteins. Vaccine efficacy was reduced 10-fold. Current YCP formulations, therefore, are not suitable for human use but have considerable potential for use in feed animal vaccines. Significantly, a YCP vaccine expressing a GFP fusion to VP1, the murine polyoma virus major capsid protein, after either oral or subcutaneous administration, protected mice against an intraperitoneal polyoma virus challenge, reducing viral DNA levels in spleen and liver by >98%.